PEDAGOGIC COMPETENCY ANALYSIS OF ELEMENTARY SCHOOL TEACHERS GROUP II AT KECAMATAN BATANG PERANAP INDRAGIRI HULU - Diana Novitasari; Zariul Antosa; Guslinda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to analyze the achievement of the pedagogical competence of group II elementary school teachers in Kecamatan Batang Peranap, Indragiri Hulu. This study involved 59 elementary school teachers and utilized descriptive quantitative method. To collect the data, the researchers utilized a questionnaire consisting of 40 positive and negative statements. Then, the data obtained were analyzed by using descriptive statistical techniques. The results of the study showed that the pedagogical ability of group II elementary school teachers in Kecamatan Batang Peranap, Indragiri Hulu was classified as high with an achievement percentage of 85.37%.